The Effect of Perceived Value and Service Quality on Customer Satisfaction: A Sustainable Growth Strategy for Digital Banks in Indonesia - Sutrisno, Ikawati Rosma; Lazuardy, Dendy (LifeSciFi, 2024)
In an era of increasingly intense business competition, it is crucial for companies to understand the factors influencing customer satisfaction and supporting sustainable growth. This study examines the influence of perceived value and service quality on customer satisfaction in the context of digital banks in Indonesia. The research employs a quantitative approach with a survey design. Data were collected through questionnaires from 97 digital bank users in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) regions using a simple random sampling technique. The sample includes 54% female and 46% male respondents, with the majority aged between 31-40 years. Data were analyzed using partial least squares structural equation modeling (PLS-SEM). The analysis results show that perceived value and service quality positively affect customer satisfaction, which can support sustainable growth for companies. Therefore, digital bank companies need to focus on enhancing perceived value and service quality to improve customer satisfaction and ensure sustainable growth. These findings highlight the importance of digital banks focusing on these aspects to enhance customer satisfaction and achieve long-term sustainable growth.